Fluid Accumulation Zone by Seismic Attributes and Amplitude Versus Offset Analysis at Solfatara Volcano, Campi Flegrei, Italy - Gammaldi, Sergio; Ismail, Amir; Zollo, Aldo (Frontiers in Earth Science, 2022)
The Solfatara crater is a quiescent volcano in the Campi Flegrei resurgent nested caldera that has been extensively investigated at its surface through active seismic investigation. The shallow evidence, such as the fumaroles of Bocca Grande e Bocca Nuova, represents one of the main markers of deep magmatic activity inside Campi Flegrei caldera (Southern Italy) and the shallower hydrothermal plume. The purpose of this work is to provide insights into the identification of the gas accumulation zone using the seismic attributes extracted from the original seismic profiles performed at the Solfatara crater. The 400-m-long profiles have been acquired during the active experiment RICEN (Repeated Induced Earthquake and Noise) along with the NNE-SSW and WNW-ESE directions across the whole surface of the crater including the main surface anomalies of the fumaroles and the Fangaia. The seismic pre-processing, pre-stack, and post-stack procedures previously applied on one of the profiles are here reproduced. The post-stack attributes time gain, envelope, energy and Root Mean Square have been computed and extracted for determining the maximum and minimum values of amplitude zones on the migrated post-stack seismic profiles. The seismic attributes are used to interpret deep reflectors, which is a geometrical attribute embedding information on faults, discontinuities, and chaotic zones. The Amplitude Versus Offset (AVO) technique has also been used as a direct gas indicator in the interpreted sections to enhance fluid discrimination and identification. All information from the original seismic profile, seismic attributes, and near-surface structural interpretation related to the Solfatara volcano has been integrated. The multi-2D image depicts fluids trapped in the Solfatara crater at depths ranging from 10 to 50 meters below the crater's surface, as well as their migration paths up to 150 meters deep: the observed reservoir has been mainly formed through the solfataric alteration of the minerals presents in the host rocks that decrease in permeability and forms and argillic phase working as cap-rock.